An Estimation of Angular Coordinates and Angular Distance of Two Moving Objects by Using the Monopulse, MUSIC, and Root-MUSIC Methods. (8th June 2011) - Rosloniec, Wojciech
Abstract : The paper presents results of extensive simulations carried out in order to assess the precision and angular resolution of subspace methods in real radar system. It has been assumed that such a system uses the 32-element uniform linear array (ULA) and radiates only 3 bursts consisting of 8 pulses in given direction. In order to avoid blind Doppler frequencies, pulse repetition interval (PRI) is different in each burst. It has been shown that change of PRI is not only necessary to avoid blind Doppler frequencies but also allows to avoid false values of angular coordinates when two objects are visible in the same beam, in the same range gate, and their echoes attain maximal values in the same Doppler filter. It has also been shown that precision and angular resolution of both MUSIC and root-MUSIC method can be improved by appropriate preprocessing of signal samples used by these methods.